A Polygonal Discontinuous Galerkin Formulation for Contact Mechanics in Fluid-Structure Interaction Problems (Communications in Computational Physics, 2021)
In this work, we propose a formulation based on the Polygonal Discontinuous Galerkin (PolyDG) method for contact mechanics that arises in fluid-structure interaction problems. In particular, we introduce a consistent penalization approach totreat the frictionless contact between immersed structures that undergo large displacements. The key feature of the method is that the contact condition can be naturallyembedded in the PolyDG formulation, allowing to easily support polygonal/polyhedral meshes. The proposed approach introduced a fixed background mesh for thefluid problem overlapped by the structure grid that is able to move independently ofthe fluid one. To assess the validity of the proposed approach, we report the results ofseveral numerical experiments obtained in the case of contact between flexible structures immersed in a fluid.
Keywords: Polygonal Discontinuous Galerkin method; fluid-structure interaction; contact mechanics.